Shear Behavior of Reinforced Concrete Two-Way Slabs with Openings - Ahmed Ashteyat; Mousa Shhabat; Ahmad Al-Khreisat; Salem Aldawsari (Buildings)
Openings in two-way reinforced concrete (RC) slabs are frequently incorporated for architectural and functional purposes, such as providing pathways for mechanical, electrical, and plumbing services. While necessary, these openings can significantly compromise the structural performance of slabs, particularly by reducing their capacity to resist punching shear, an effect that is especially critical when the openings are located near column–slab connections. This paper provides a detailed review of the existing research, examining how various opening parameters such as their size, shape, and position affect key structural performance metrics including their stiffness, ductility, and failure modes. The findings highlight that opening geometry is a major determinant of a slab’s overall behavior. Notably, the proximity of openings to column faces is identified as a critical factor that can substantially influence the extent of strength degradation and failure mechanisms. Furthermore, this review identifies a significant research gap concerning the behavior of slabs with openings under non-standard loading conditions, such as seismic activity, blasts, and impact loads. It also emphasizes the need for further investigation into the long-term performance of such slabs under adverse environmental influences, including elevated temperatures, corrosion, and material degradation. By consolidating the current knowledge and identifying unresolved challenges, this review aims to guide engineers and researchers in developing more robust design strategies and performance-based solutions for RC slabs with openings, ultimately contributing to safer and more resilient structural systems.